Blockade of AMPA Receptor Regulates Mitochondrial Dynamics by Modulating ERK1/2 and PP1/PP2A-Mediated DRP1-S616 Phosphorylations in the Normal Rat Hippocampus - Kim, Ji-Eun; Choi, Hui-Chul; Song, Hong-Ki; Kang, Tae-Cheon (Frontiers in Cellular Neuroscience, 2019)
N-methyl-D-aspartate receptor (NMDAR) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) activations induce fast and transient mitochondrial fragmentation under pathophysiological conditions. However, it has been still unknown whether NMDAR or AMPAR activity contributes to mitochondrial dynamics under physiological conditions. In the present study, MK801 (a non-competitive NMDAR antagonist) did not affect mitochondrial length in hippocampal neurons as well as phosphorylation levels of dynamin-related protein 1 (DRP1)-serine (S) 616, extracellular-signal-regulated kinase 1/2 (ERK1/2), c-Jun N-terminal kinase (JNK), p38 mitogen-activated protein kinase (p38 MAPK) and AMPAR. In contrast, perampanel (a non-competitive AMPAR antagonist) elongated mitochondrial length in neurons concomitant with diminishing phosphorylations of DRP1-S616, ERK1/2, and JNK, but not p38 MAPK. Perampanel also reduced protein phosphatase (PP) 1, PP2A and PP2B phosphorylations indicating activations of these PPs, which were unaffected by MK801. U0126 (an ERK1/2 inhibitor) elongated mitochondrial length, accompanied by the reduced DRP1-S616 phosphorylation. SP600125 (a JNK inhibitor) did not influence mitochondrial length and DRP1 phosphorylations. Okadaic acid (a PP1/PP2A inhibitor) reduced mitochondrial length with the up-regulated DRP1-S616 phosphorylation, while CsA (a PP2B inhibitor) increased it with the elevated DRP1-S637 phosphorylation. Co-treatment of okadaic acid or CsA with perampanel attenuated the reductions in DRP1-S616 and -S637 phosphorylation without changing DRP1 expression level, respectively. GYKI 52466 (another non-competitive AMPAR antagonist) showed the similar effects of perampanel on phosphorylations of DRP1, ERK1/2, JNK, PPs and GluR1 AMPAR subunits. Taken together, our findings suggest that blockade of AMPAR may regulate the cooperation of ERK1/2- and PP1/PP2A for the modulation of DRP1 phosphorylations, which facilitate mitochondrial fusion.